Topeng Patih Dance: A Manifestation of the Beginning of Human Life in the Malang Mask Puppet’s World - Wido Minarto, Soerjo; Desta Rahmanto, Kelik (KnE Social Sciences, 2020)
The focus of the study in this research was the Patih Mask dance in the Malang Masked Puppet performance as the opening dance. This dance has a close relationship with space, time, and content in the structure of the show. The purpose of this study is to examine the expression of aesthetic concepts through the structure of artistic symbols in the performance of Malang Masked Puppet. This research used ethnographic methods by emphasizing structural and hermeneutic theories. The aesthetic symbols that are reflected in the unity of the show consist of the ritual concept, characterization, communication, dance moves, make-up and fashion, accompaniment music, and elements of the stage which all lead to a noble behavior. The whole unity of the elements is a symbol of ”Sangkan Paran”. Keywords: Symbols, beginning, Sangkan Paran, Patih Mask, Malang Mask Puppet